Design of an Arabic Interactive Learning Multimedia Application Using the MDLC Method - Fitriansyah, Ahmad; Aprianto, Iwan; Nugroho, Prasetyo Adi (Universitas Mohammad Husni Thamrin, 2025)
The Indonesian government through educational institutions has made various efforts to teach the language. Apart from Indonesian and regional languages, languages ​​such as English, Arabic and Mandarin are some of the languages ​​that will be taught to students. Arabic language learning at Madrasah Tsanawiyah Istiqlal Jakarta is going well, although there are still many students who have difficulty learning Arabic and tend to prefer English lessons. Some students find Arabic lessons difficult to understand. Easy and fun Arabic learning applications are needed to increase student interest. This research aims to produce a design for an interactive Arabic learning multimedia application. The method used is the Multimedia Development Life Cycle (MDLC) which consists of six phases, namely concept, design, material collection, production, testing and distribution. Use-case modeling is used to show application modeling where users can access several features provided by the application. The first testing stage uses the black box method by testing the application based on system responses such as the intro display, main page and buttons on the application. The second stage of beta testing consists of testing user acceptance of the application for Madrasah Tsanawiyah Istiqlal Jakarta students. Both stages of testing show that the application runs well and can be used correctly by users. User testing was carried out by calculating questionnaires from MTs Istiqlal Jakarta students which resulted in a score of 86.68%. This score shows that the usability aspect of Arabic language learning media is suitable for use.